Biomass Transportation Model for Intermodal Network - MD Sarder; Ziaul Adnan; Chad Miller (International Journal of Supply Chain Management, 2013)
Biomass transportation suffers from higher transportation costs and insufficient competition in terms of supply chain providers. The transportation network optimization is somewhat absent in biomass transportation and hence this sector is still subsidized in many states. Biomass transportation industry can be benefitted from utilizing intermodal facilities and various transportation modes. Availability of several modes introduces flexibility of routing and intermodal facility enables using several modes throughout the routes. Transportation network consisting intermodal facility connected with various modes along with various shipment options (direct shipment, transshipment, cross docking, consolidation etc.) among different stages of biomass transportation offer more alternative choices for consideration. Some of the alternative choices induce less cost with prolonged service time, some choices provide expedite delivery with higher cost, some choices maintain similar service level and on time delivery at a reasonable or moderate cost. Proper analysis of various routing options should be done in order to choose the most efficient one. In most of the cases, minimization of time leads toward a costly transportation, on the other hand cost saving routes requires more time to ship the order. This research endeavors to develop a methodology so that both of the objectives (i.e. minimization of transportation time and minimization of transportation cost) can be satisfied together to find out an optimal transportation solution. This paper considers the supply chain of cellulosic bio-diesel. This supply chain consists of harvesters, hub or storage facilities, preprocessing facilities and bio-refinery plant. Several modes of transportations and intermodal facilities are available in the supply chain. There are direct shipment and transshipment options too. This paper tried to develop a generic mathematical model to find out the optimal solution for both minimization of transportation cost and time. In this paper, excel solver is used to calculate the numbers of unit loads to be transported through various routes. Finally, it compares three solutions, out of which, one gives the minimum cost, another gives the minimum time and last one is the modification of second solution that costs less than the second one. The modification is done by choosing alternative cost saving routes without affecting the critical time. The recommended solution considers the trade-off between time and cost. It is expected, that this research will assist the decision maker of biomass industry to make smart choice in route and mode selection process.